Rapid detection of Vancomycin-Resistant Enterococci (VRE) in rectal samples from patients admitted to intensive care units - d'Azevedo,Pedro Alves (2009)
The reduction in time required to identify vancomycin-resistant enterococci (VRE) has gained increased importance during hospital outbreaks. In the present study, we implemented a laboratory protocol to speed up the VRE screening from rectal samples. The protocol combines a medium for selective VRE isolation (VREBAC®, Probac, São Paulo) and a multiplex PCR for detection and identification of vanA and vanB resistance genes. The screening performance was analyzed in 114 specimens collected from four intensive care units. The swabs were collected at two periods: (1) during a VRE outbreak (February 2006, n=83 patients) and (2) at the post-outbreak period, after adoption of infection control measures (June 2006, n=31 patients). Forty-one/83 VRE (49.4%) and 3/31(9.7%) VRE were found at the first and second period, respectively. All isolates harbored the vanA gene. In both periods, detection of the gene vanA parallels to the minimum inhibitory concentration values of >256 µg/mL and >48 µg/mL for vancomycin and teicoplanin, respectively. Multiplex PCR and conventional methods agreed in 90.2% for enterococci identification. Besides this accuracy, we also found a remarkable reduction in time to obtain results. Detection of enterococcal species and identification of vancomycin resistance genes were ready in 29.5 hours, in comparison to 72 hours needed by the conventional methods. In conclusion, our protocol identified properly and rapidly enterococci species and vancomycin-resistance genes. The results strongly encourage its adoption by microbiology laboratories for VRE screenning in rectal samples.